CAUSAL FACTORS OF DISHARMONY ISSUES ON LICENSING COASTAL RECLAMATION IN SAMPANG AND BANGKALAN REGENCIES - Rina Yulianti; Mufarrijul Ikhwan (Faculty of Law, Universitas Jenderal Soedirman, 2018)
This research is to investigate the contributing factors on the disharmony of licensing coastal reclamation in Sampang and Bangkalan Regencies. Socio legal research approach was used through indepth interviews and observations. The study was conducted in areas with reclamation activities and subsequently considering the relevant documents to analyze as the secondary data. The findings of this research demonstrate factors leading to disharmony of licensing coastal reclamation: the regional government of Sampang and Bangkalan regencies has not synchronized the reclamation policies with the presidential regulation. Reclamation in Sampang and Bangkalan are not based on the Presidential Regulations Number 122 Year 2012 on the Licensing Coastal Reclamation. The license of reclamation in Sampang should have been issued by district or provincial government instead of by the head of village. Reclamation license in Bangkalan should have been issued by the Ministry of Maritime Affairs and Fisheries because it is located in the National Strategic Areas. The fact, it was granted by the local government. Harmonization consequently becomes an important part to construct an integrative law for realizing central and local authority’s conformity in introducing the policy to control of coastal spatial utilization. Keywords: coastal, disharmony, licensing, reclamation.